Frequency and Clinical Outcomes of Women with Postpartum Hemorrhage at a Tertiary Care Hospital - Bushra Begum Ramejo, Mubashir Ahmed Ramejo, Sanober Soomro, Mehtab Ali Tunio, Musharraf Ahmed Ramejo, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: Postpartum hemorrhage (PPH) is still a leading cause of maternal morbidity and mortality globally. Postpartum hemorrhage is characterized as excessive bleeding (> 500 ml) from the vaginal tract following childbirth. The present study aimed to determine the frequency and clinical outcomes of women with postpartum hemorrhage. Materials and Methods: This cross-sectional study was conducted on 1346 patients who underwent vaginal delivery in the department of obstetrics and gynecology, Kausar Hospital, Khairpur Mirs from March 2021 to March 2022. The study included all the women who had postpartum hemorrhage following vaginal birth in the labor room or who were referred with primary postpartum hemorrhage. Patients with prior history of bleeding disorders and on warfarin were excluded from the study. SPSS version 26 was used for data analysis. Results: Of the total 1346 patients, the prevalence of postpartum hemorrhage was 12.6% (n=170). Out of 170 PPH cases, the incidence of primary and secondary PPH was 138 (81.2%) and 32 (18.8%) respectively. The age-wise distribution of patients were as follows: 26 (15.3%) had <20 years, 62 (36.4%) in 21-30 years, 68 (40.1%) in 31-40 years, and 14 (8.2%) in >40 years. The incidence of primiparas, multipara, and grand multipara were 34 (20%), 58 (34.1%), and 78 (45.9%) respectively. The booked and unbooked patients were 56 (32.9%) and 114 (67.1%) respectively. Among 170 PPH patients, the incidence of spontaneous vaginal delivery, instrumental delivery, and cesarean section were 52 (30.6%), 56 (32.9%), and 62 (36.5%) respectively. The major causes of PPH was uterine atony, perineal and vaginal tears, and prolong labor found in 112 (65.9%), 56 (32.9%), and 38 (22.4%) respectively. Conclusion: The present study concluded that the prevalence of PPH was 12.6% among total cases. Primary PPH was more prevalent than secondary PPH and uterine atony was the most common cause followed by perineal and vaginal tears and prolong labor. Additionally, unbooked patients were more susceptible to PPH. Risk factors assessment, unnecessary induction, and third stage labor active management can prevent the PPH. Keywords: Postpartum hemorrhage, Clinical outcomes, Uterine atony